2003
DOI: 10.1081/pln-120018560
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Caloric Energy Distribution and Variations in Two Rice Varieties Related to Different Nitrogen Application Levels in Paddy Field

Abstract: A field experiment was conducted in Hangzhou, Zhejiang Province, P.R. of China in 1999 to investigate the quantitative caloric energy characteristics of two rice cultivars (Oryza sativa L.), early crop rice Jia yu 948 and late crop rice Jia yu 93390 were grown in different nitrogen levels and climate conditions. The two cultivars were grown with 0, 80, 120, 160, and 200 kg ha À1 of nitrogen fertilizer and in ample water and farming management activities. Analysis of caloric energy showed that significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The relative sink size of the husk varied among the cultivars. Husk was found to contain much more caloric energy which supports grain development, compared with the caryopsis 23. The high caloric energy is the product of photosynthesis which requires Fe as the electron transporter in this system 24.…”
Section: Discussionmentioning
confidence: 95%
“…The relative sink size of the husk varied among the cultivars. Husk was found to contain much more caloric energy which supports grain development, compared with the caryopsis 23. The high caloric energy is the product of photosynthesis which requires Fe as the electron transporter in this system 24.…”
Section: Discussionmentioning
confidence: 95%
“…Caloric content differed between pairs of species with exception of N. cuspidata and C. brasiliensis. Yang et al (2003) reported that caloric values varies among plant species and within species in different environments, due to chemical composition of the organic substances (Lin et al, 2007). It is noteworthy that plants that grow better and can achieve higher biomass presents higher caloric content (Yajing et al, 2007).Major caloric content was recorded for Nectandra cuspidata (17.8 KJ.g -1 to 23.7 KJ.g -1 dry weight).…”
Section: Discussionmentioning
confidence: 99%
“…ENERGY MEASUREMENT. Caloric values were measured according to the method described by Long (1934) and Yang et al (2003). Oven-dried ground tissue samples of 1 g or less were used.…”
Section: Chlorophyll Measurementmentioning
confidence: 99%